The antiquarian's object of desire - Holton, India (Holton, India. Love's academic (Series), 2026)
"When two history professors and best friends are forced to fake hate to protect their reputations, chaos ensues, in this rollicking historical-fantasy rom-com. Magical-antiques experts Amelia Tarrant and Caleb Sterling have been best friends forever, although lately each has begun secretly wishing for more than friendship. But when rumors about their relationship spread, they're forced to fake being enemies to protect their reputations and keep their jobs. The resulting arguments spark havoc across Oxford University, and when they cause an explosion while fighting over a magical antique, it's the final straw for their exasperated faculty head. He dispatches them to a job in Cumbria where even they can't get into trouble. It proves just how wrong one man can be. In a stormbound old-manor house, Amelia and Caleb face magical mayhem and rampaging ghosts that make the previous havoc look mild in comparison. Most troublesome of all, though, is the secret of how they feel about each other. When it comes to tackling deadly antiques, hiding the truth in their hearts could destroy them for real"-- Provided by publisher.